Effect of Particle Size and Extraction Time on Total Flavonoid Level of Artemisia vulgaris Ethanol Extract - Kurniasih, Kholif Sholehah Indra; Arifah, Mitsalina Fildzah; Setiyawati, Eka Ayu; Rahmah, Syafira Atika; Widianingrum, Lucia; Kholifah, Eva (Journal of Biotechnology and Natural Science, 2024)
Background: Artemisia vulgaris, also referred to as Daun Baru Cina, is a herbaceous species within the Asteraceae family. Artemisia vulgaris is a traditional remedy for numerous ailments, exhibiting anti-inflammatory and antioxidant properties due to its secondary metabolites, specifically flavonoids. The extraction method is essential for extracting the desired chemical from natural sources intended for therapeutic use. The extraction process is affected by several elements, including the particle size of simplicia powder and the duration of extraction. Objective: This study aims to test the effect of differences in particle size of powdered simplicia and extraction time of Artemisia vulgaris leaves on total flavonoid levels, using 70% ethanol solvent. Researchers used a quantitative approach using a descriptive research design. In this study, a qualitative test was carried out in the form of phytochemical screening followed by a quantitative test to determine the total flavonoid levels of Artemisia vulgaris leaves. Various particle sizes (40 mesh and 80 mesh) and extraction times (12 hours and 36 hours) were used in this study. Using ultraviolet-visible spectrophotometry, the Total Flavonoid Level (TFC) of the ethanol extract of Artemisia vulgaris leaves was determined. Results: The TFC value obtained for the optimal particle size was 40 mesh, with an extraction time of 12 hours, which was 72.073 ± 1.126 mgQE / g extract. While 80 mesh, with an extraction time of 36 hours, gave a TFC value of 70.169 ± 0.480 mgQE / g extract. In addition, 70% ethanol extract of Artemisia vulgaris leaves contains secondary metabolites of phenolic alkaloids, tannins, saponins, and steroids. Conclusion: The study concludes that the quantity of simplicia powder particles and the extraction duration influence the total flavonoid concentrations in Artemisia vulgaris.